Experimental research on car movement characteristics under the condition of different driving emotions. (December 2018) - Wang, Xiao-yuan; Liu, Ya-qi; Liu, Li-ping; Wang, Fang; Kong, Dong; Wang, Yun-yun
Emotion is the external way to express human's inner thoughts, which has a significant influence on human behaviors. It is an important prerequisite for studying the intrinsic affect mechanism of emotions on behaviors certain. In this article, drivers' emotional induction experiment, actual and virtual driving experiments are designed to obtain the multi-source dynamic data of human–vehicle–environment under the condition of different emotions. The influences of emotions' changes on car movement characteristics of different types of drivers are explored. Changing law of car movement characteristics under the condition of different emotions can be obtained finally. The research can provide theoretical basis for the future research of driver assistance system, which is of great significance to realize active vehicle safety warning and unmanned driving in the future.